Overlooked Enterobacterales as hosts of antimicrobial resistance in aquatic environments - Anca Farkas; Anca Butiuc-Keul; Rahela Carpa; Edina Szekeres; Adela Teban-Man; Cristian Coman (Scientific Reports)
Abstract The increasing frequency of antibiotic resistant bacteria and their dissemination in environmental microbiomes is a critical health concern. Water quality assessment and AMR surveillance are broadly focused on commonly found Enterobacterales, and mainly on the faecal indicator E. coli. In this study, we analysed antibiotic resistance and biofilm formation in 14 environmental isolates belonging to six neglected species. Genetic diversity was assessed by ERIC-PCR. Identified as Cronobacter sakazakii (1), Kluyvera intermedia (1), Leclercia adecarboxylata (1), Raoultella ornithinolytica (8), Raoultella terrigena (1), and Yersinia massiliensis (2), each isolate had a unique and distinct AMR profile. The isolates demonstrated intrinsic resistance to erythromycin and increased resistance to ampicillin and tetracycline. None of the isolates exhibited carbapenem resistance. Ten isolates were MDR. Thirteen out of the 24 investigated ARGs were detected in bacterial genomes. Except for carbapenemases, various β-lactamases (bla TEM, bla CTX-M), and also tet, sul, erm, mef and qnr genes were found. A strong positive correlation was observed between the phenotypic and genotypic resistance. Due to its discriminatory power at the taxonomic level, ERIC-PCR fingerprinting provided a reliable and accurate molecular typing. Negative correlations between the number of ERIC bands, the magnitude of resistance and the biofilm score indicate that strains with abundant ERIC sequences are less likely to be resistant and to adhere to surfaces. This suggests that a high genome plasticity and adaptability prevents specific survival strategies and deserves further attention.